ESTRATEGIAS DE GESTIÓN DE COMUNIDADES EN LA CONSTRUCCIÓN DE MARCA Y LA PARTICIPACIÓN DEL USUARIO EN PLATAFORMAS DIGITALES - ROSADO COTTO, NAYELLY VERONICA (2024)
This research deals with community management in brand building and user participation in current digital platforms, where the importance of establishing adequate communication with the target market to increase business competitiveness is highlighted. In addition, the study highlights the benefits of developing optimal work as a Community Manager, which is the professional in charge of managing community management and implementing favorable actions that allow increasing interaction with the user and strengthening the brand. The objective of the research is to analyze community management strategies in brand construction and user participation in digital platforms. The study methodology is made up of a mixed approach; that is, qualitative and quantitative; In addition, the hypothetical deductive and analytical inductive methods were used. Survey and observation techniques were also considered, which are aimed at 38 restaurants that are part of the Abreco community in the city of Babahoyo. The research concluded that: The proper management of digital platforms is very important since currently one of the most effective ways to build a brand is through social networks. Constant exposure in these digital media contributes to increasing the visibility of the brand, generating greater recognition and reach.